2023
DOI: 10.2196/48850
|View full text |Cite
|
Sign up to set email alerts
|

Risk, Trust, and Emotion in Online Pharmacy Medication Purchases: Multimethod Approach Incorporating Customer Self-Reports, Facial Expressions, and Neural Activation

Semra Ersöz,
Anika Nissen,
Reinhard Schütte

Abstract: Background Online pharmacies are used less than other e-commerce sites in Germany. Shopping behavior does not correspond to consumption behavior, as online purchases are predominantly made for over-the-counter (OTC) medications. Objective The objective of this study was to understand the purchasing experiences of online pharmacy customers in terms of critical factors for online pharmacy adoption. Methods Thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…Research from other countries has indicated that the perception of risk versus trust towards online pharmacies are important for the consumers experience towards buying medicines online [8] and that digital pharmaceutical marketing as well as convenience are important factors for the consumers decision making when it comes to buying OTC medicine online [9,26].…”
Section: Predictors Of Online Shopping Of Medicinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research from other countries has indicated that the perception of risk versus trust towards online pharmacies are important for the consumers experience towards buying medicines online [8] and that digital pharmaceutical marketing as well as convenience are important factors for the consumers decision making when it comes to buying OTC medicine online [9,26].…”
Section: Predictors Of Online Shopping Of Medicinesmentioning
confidence: 99%
“…Among the Swedish public, there is a tendency that more and more people purchase medicines online [7]. However, knowledge about the demand side is scarce and insufficient to delineate reasons why people choose to purchase medicines online instead of at physical pharmacies [7][8][9]. In the present study, we draw on findings from a national representative survey with the aim of examining the characteristics of the Swedish public who buy medicines online.…”
Section: Introduction 1backgroundmentioning
confidence: 99%